Fifatrol, An Ayurvedic Formulation- A Prospective Multi-Center Observational Study On The Symptoms of Upper Respiratory Tract Infections - Verma, Santosh Kumar; Haye, Abdul; Saxena, Shubham; Junaid, Mohammad; Sharma, Mukesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Background: Upper respiratory tract infections (URTI) is a leading cause of economic burden as it remains among the top 3 diagnosed diseases globally with an estimated annual cost above 22 billion. Available medications to treat URTI and associated symptoms are effective, however, their tolerability remains a challenge for the practitioners. Recently, the use of alternative and complementary therapy has increased for the management of URTI symptoms. Fifatrol is an ayurvedic formulation for the management of URTI and its associated symptoms. However, its evidence-based data is limited. Therefore, this observational study was aimed to investigate the effects and to assess the safety of Fifatrol on URTI symptoms. Method: A post-marketing prospective observational study was carried out in the various cities of India. Patients enrolled in the study were presented with the symptoms of URTI in the health care centers and prescribed Fifatrol in twice-daily dose by the practitioners voluntarily. Symptoms of URTI (local, general, total) were collected on a 0–7 Likert scale at three-time points within 1 week (1st day, 4th day, and 7th day), using a questionnaire. Effectiveness was evaluated by examining the reduction in symptoms scores at day 4 and 7 respectively from baseline (day 1) Results: The mean score of local symptoms was 19.49 (SE: 0.39) on the day 1, dropping to 6.82 (SE: 0.14) and 1.84 (SE: 0.04), showing a decrease of 65.0% and 90.55% on the 4th and 7th day respectively (p < 0.001). The mean score of general symptoms reduced from 8.06 (SE: 0.26) on day 1 to 1.62 (SE: 0.5) and 0.8 (SE: 0.03), revealing a reduction of 79.9% and 90.11% on the 4th and 7th day respectively (p < 0.001). The mean total score of symptoms reduced from 28.34 (SE: 0.59) on day 1 to 8.63 (SE: 0.15) and 2.73 (SE: 0.05), indicating a decrease by 69.5% and by 90.36% on the 4th and 7th day respectively (p < 0.001). 1.97% adverse events of mild intensity reported during the observation period. Conclusions: This observational study has gathered evidence about the effectiveness and safety of Fifatrol on the amelioration of the symptoms of URTI.